Online Learning with Google Forms Included with Youtube and Link Material - Masnurul Shalihah (research, training and philanthropy institution Natural Aceh, 2021)
The increasing number of people infected with the corona virus causes the disruption of the face-to-face learning process directly, because it can cause the emergence of new corona virus clusters in schools. As a substitute is the implementation of an Online learning system. The purpose of this research is to improve student learning outcomes in online learning using a combination, google form, youtube and material links. This research method is in the form of data collection on the value of student learning outcomes that are analyzed in a descriptive and classical manner using a formula to find the presentation of student learning outcomes. The benefit of this research is that it can be used as a reference for exploring the concept of Google Forms, Youtube and Link Material in online learning. The results of this study indicate that online learning using a combination of google form, youtube and material links can improve learning motivation, learning activities and improve student learning outcomes.